Knowledge graphs and language technology : ISWC 2016 International Workshops: KEKI and NLP & DBpedia, Kobe, Japan, October 17-21, 2016, Revised selected papers /: ISWC 2016 International Workshops: KEKI and NLP & DBpedia, Kobe, Japan, October 17-21, 2016, Revised selected papers. (2017) - Unknown
No abstract available